PKM Pelatihan Dan Pendampingan Inovasi Produk Teng Teng Rumahan Desa Tarikolot Sumedang - Denni Pratama; Bani Nurhakim; Ade Rizki Rinaldi; Arman Maulana; Cistia Ningrum (CV. Multi Kreasi Media, 2023)
Tarikolot Village in Sumedang is known for producing a traditional snack, teng teng, which has a unique flavor but lacks widespread recognition in modern markets. The challenges faced by teng teng artisans include limited product innovation and marketing strategies, resulting in stagnant income. Through this Student Creativity Program (PKM), training and mentoring are provided to enhance the quality and variety of teng teng products, making them more appealing to consumers. The objective of this activity is to equip the artisans with the knowledge and skills to develop product innovations and effective marketing strategies, enabling them to compete in a broader market. The methods employed include theoretical and practical training on creating teng teng with innovative flavors and packaging, as well as mentoring in designing digital marketing strategies. The expected outcomes of this activity are improved product quality, diversified product offerings, and enhanced marketing knowledge and skills among the artisans. It is anticipated that this program will increase the competitiveness of teng teng products in local and national markets, contributing to the economic well-being of the Tarikolot Village community.